Polyphenol Profile and Antioxidant, Antityrosinase, and Anti-Melanogenesis Activities of Ethanol Extract of Bee Pollen - Qiang He; Jie Wang; Jingjing Li; Wenchao Yang (Pharmaceuticals)
Background/Objective: Bee pollen, a rich nutritional food, was employed to develop a raw material for skin whitening. Methods: The polyphenol profile and antioxidant, antityrosinase, and anti-melanogenesis activities of the ethanol extracts of five species of bee pollens (EEBPs) were determined. Results: The results showed that there were a total of 121 phenolic compounds in these EEBPs. Each type of bee pollen had unique substances. The best anti-melanogenesis activity was observed for sunflower EEBP, about 25% at a concentration of 25 μg/mL BEEP. The anti-melanogenesis activities of EEBPs from high to low were sunflower, apricot, camellia, rapeseed, and lotus EEBPs. The anti-melanogenesis activity in B16F10 cells was positively correlated with the antityrosinase activity and total phenol content, with coefficients of 0.987 and 0.940. The Kyoto Encyclopedia of Genes and Genomes enrichment analysis results of untargeted proteomics revealed that sunflower EEBP inhibited melanogenesis in B16F10 cells by reducing the expression of the proteins MAP2K1, NFKB2, RELB, RPS6KA3, CASP3, TRAF6, MAP2K5, MAPKAPK3, STRADA, CCNA2, and FASN involved in the cAMP, MAPK, and TNF signaling pathways, even though these pathways were not significantly different from the control group. Conclusions: The sunflower EEBP has high inhibition effect on melanogenesis than other species EEBPs. The results provide a basis for the future industrial development of a raw material for skin whitening.